Development of an Information System for Vehicle Registration Services via LINE Official Account - ทวีประสิทธิ์ เพ็ญนภา; ทวีประสิทธิ์ เพ็ญนภา; ปานสุวรรณ ดุสิตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to (1) develop an information system for vehicle registration services via LINE Official Account and (2) evaluate the system quality and user satisfaction. The sample included three information technology experts and 30 service users. Research instruments comprised the developed LINE Official Account system, a system quality evaluation form, and a five-point Likert scale user satisfaction questionnaire. Data were analyzed using mean and standard deviation. The findings revealed that the system effectively provided information, automated responses, document and fee notifications, and online appointment booking as intended. Expert evaluations indicated high system quality (x̄= 4.50, S.D. = 0.51), and user satisfaction was also rated high (x̄= 4.35, S.D. = 0.65), demonstrating that the system is practical and enhances the provision of vehicle registration services.